Synthesis of Chiral Hypervalent Trifluoromethyl Organobismuth Complexes and Enantioselective Olefin Difluorocarbenation Screenings. Issue 2 (13th February 2023) - Louis‐Goff, Thomas; Trinh, Huu Vinh; Chen, Eileen; Rheingold, Arnold L.; Hyvl, Jakub
Abstract: Two hypervalent trifluoromethyl organobismuth complexes were prepared from commercially available chiral amines, ( R )‐1‐cyclohexylethylamine and ( 1R, 2R, 3R, 5S )‐(−)‐isopinocampheylamine; however, only the complex from the latter amine was prepared as a single stereoisomer. Both organobismuth complexes were fully characterized by NMR spectroscopy and single‐crystal X‐ray crystallography, revealing that the structures were similar to previously reported complexes with a hypervalent Bi−N bond. The complexes were catalytically active in olefin difluorocarbenation with Ruppert‐Prakash reagent (TMS‐CF3 ) used as a terminal source of CF2 . The catalyst derived from isopinocampheylamine was screened with three prochiral olefins of various reactivity in DCM and toluene. All reactions afforded the 1, 1‐difluorocyclopropanes in good yields, but no enantiomeric excess was observed. Abstract : Progress toward enantioselective difluorocyclopropanation : This work presents synthesis and characterization of chiral hypervalent trifluoromethyl organobismuthanes. One complex was synthesized as a single stereoisomer and was screened in catalytic olefin difluorocarbenation with prochiral olefins and TMS‐CF3, as a terminal source of CF2 . The screened catalyst showed a good catalytic activity; however, enantiomeric excess in the formed 1, 1‐difluorocyclopropanes was not observed.